ANALYSIS OF PUMP INSTALLATION DESIGN FOR CLEAN WATER IN PT PAMAPERSADA NUSANTARA, INDO DISTRICT - BONTANG, EAST KALIMANTAN - Moh. Arif Batutah; Hairul Huda (Universitas Mulawarman, 2022)
The demand for clean water by company employees who live in barracks is changing. This change in direction also affects the distribution of clean water, which will impact the effectiveness of the plumbing and pump systems. This analysis aims to know the plumbing installation and selection of the right pump so it can operate optimally. The method used is the analysis by ignoring losses, such as friction losses between the working fluid and the equipment. This analysis also calculates head, capacity, pump power, and efficiency. From the calculation result, we conclude that the flow capacity is 2,643 m3/min, and the total head installation is 71,69 m. So, a centrifugal pump with rotation 2951 rpm, type Groundfos CRN 90 4-2, is the best pump for installation. Keywords: pump, head installation, pump power, efficiency, capacity